2013
DOI: 10.1111/aji.12134
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Stromal Cell-Derived Factor-1 Reduces Neoangiogenesis in Human Endometriosis Lesions in a Mouse Model

Abstract: Blocking SDF-1 reduces neovascularization and survival of lesions in a mouse model of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
13
0
2
Order By: Relevance
“…The cytokine profile suggests a potential involvement of IL-17A in mediating neo-angiogenesis and recruitment of lymphocytes and bone-marrow derived cells to the site of lesion development. In earlier studies, we (31) and others (32) showed that CXCL12 contributes to the recruitment of endothelial progenitor cells at the endometriotic lesions and aid neo-angiogenesis.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The cytokine profile suggests a potential involvement of IL-17A in mediating neo-angiogenesis and recruitment of lymphocytes and bone-marrow derived cells to the site of lesion development. In earlier studies, we (31) and others (32) showed that CXCL12 contributes to the recruitment of endothelial progenitor cells at the endometriotic lesions and aid neo-angiogenesis.…”
Section: Resultsmentioning
confidence: 84%
“…Concentrations of cytokines such as TNF-α, IL-6 and IL-8 are increased in the peritoneal fluid and are augmented in production from activated peritoneal macrophages, which primarily contribute to the inflammatory milieu associated with pathogenesis of the disease. Furthermore, secretory factors from immune cells mediate vascularization of endometriotic lesions through both neo-angiogenesis stimulated by VEGF (30) and de novo vasculogenesis at the site of implantation through recruitment of bone-marrow derived endothelial progenitor cells (EPCs) (31, 32). Emerging evidences from cancer and autoimmune literature suggest that IL-17A contributes to the neo-angiogenesis and perpetuates inflammatory responses (25, 33), but there are few reports investigating the role of IL-17A in the pathogenesis of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Stromal cellderived factor-1/chemokine receptor type-4 signaling, in turn, also regulates the homing of EPCs to endometriotic lesions. 15,48 In addition, our gene expression profile analysis revealed a strong up-regulation of the genes coding for early growth response 3, nuclear receptor corepressor 2, and plasma kallikrein B1 in estrogen-treated lesions. Both early growth response 3 and nuclear receptor corepressor 2 have been shown to promote angiogenesis.…”
Section: Epcs In Endometriosismentioning
confidence: 79%
“…Not surprisingly, we also observed significant increase in PECAM1, CXCL10 , and CXCL12 (genes known to play role in angiogenesis) in ectopic tissues compared with eutopic and control endometrium. Indeed, we previously reported increased expression of CXCL12 protein in human endometriotic lesions compared with matched eutopic endometrium samples and demonstrated that blocking of CXCL12 in a xenograft mouse model of endometriosis affects neovascularization and survival of endometriotic lesions (29). To this end, these immune gene profiles further support that ectopic endometriotic lesion is viewed as foreign, elicits local inflammation, establishes vasculatures, and participates in the generation of pain for some patients, as suggested by increased PTGER4 expression in ectopic tissues.…”
Section: Discussionmentioning
confidence: 99%